The Influence of Implementing Risk-Based Business Licensing (OSS RBA) on Investment Growth in the Food and Beverage Services Subsector in Medan City - Farosa, Delfi; Badaruddin, Badaruddin; Irmayani, Tengku (Universitas Medan Area, 2024)
This research examines the business growth of the Food and Beverage Services subsector in Medan City along with the implementation of the Risk-Based Licensing System (OSS RBA) in Indonesia. OSS RBA based on the Standard Qualifications for Indonesian Business Fields (KBLI) aims to increase the Ease of Doing Business (EoDB). However, the application of top-down OSS RBA with the Business Identification Number (NIB) carries the potential for abuse. This research analyzes the factors (Starting a Business, Electricity Connection, Tax Payments, Building Permits, Access to Credit, and Protection of Minority Investors) that influence the Growth of Food and Beverage Services Investment in Medan City. The results of the Confirmatory Factor Analysis (CFA) show three significant factors: Protection of Minority Investors, Starting a Business, and Access to Credit. Obstacles include the NIB scale not being by local spatial planning and changes in the issuance of risk permits between the Central and Regional Governments. It is hoped that this research will provide insight into the implementation of OSS RBA and investment growth in the Food and Beverage Services sector.